Assessment of Wound Healing Activity of Green Synthesized Titanium Oxide Nanoparticles using Strychnos spinosa and Blighia sapida - H. Hassan; K.I. Omoniyi; F.G. Okibe; A.A. Nuhu; E.G. Echioba (Journal of Applied Sciences and Environmental Management, 2020)
The biosynthesis of nanoparticles has been proposed as a cost effective and environmentally friendly alternative to chemical and physical methods. The present work investigates the synthesis of titanium oxide nanoparticles (TiO2 NPs) by green approach using Strychnos spinosa and Blighia sapida leave extracts. The detailed characterization of the TiO2 NPs was carried out using UV-Visible Spectroscopy, Scanning Electron Microscopy (SEM), X- ray Diffraction (XRD), and Fourier-Transform Infrared (FTIR) Spectroscopy. The green synthesized TiO2 NPs excitation was confirmed using UV–Vis spectrophotometer at 270 and 290 nm for Strychnos spinosa and Blighia sapida respectively. SEM revealed that the synthesized TiO2 NPs were spherical and crystalline in nature. The overall sizes are 40 and 50 nm for Strychnos spinosa and Blighia sapida respectively. FTIR spectroscopic analysisshowed the presence of flavonoids, polyphenols and amide groups likely to be responsible for the green synthesis of titanium oxide nanoparticles using S. Spinosa and B .sapida aqueous leaf extracts. The XRD pattern showed the characteristic Bragg peaks of (111), (200), (220) and (311) facets of the anatase titanium oxide nanoparticles and confirmed that these nanoparticles were crystalline and spherical in nature. Furthermore, the green synthesized TiO2 NPs wound healing activity was examined in the excision wound model by measuring wound closure, histopathology and protein profiling. This revealed significant wound healing activity in Albino rats. In the present study, topical application ofnanoformulated extracts of B. sapidaa nd S. spinosa significantly accelerated wound healing with 20% nanoformulated ointment having the highest percentage wound contraction ability comparable with gentamicin (a commercially sold antimicrobial agent used in dressing wounds). In conclusion, this work proved the capability of using TiO2 NPs to deliver a novel therapeutic route for wound treatment in clinical practice.